2023
DOI: 10.3390/brainsci13050720
|View full text |Cite
|
Sign up to set email alerts
|

Improved Spatial Knowledge Acquisition through Sensory Augmentation

Abstract: Sensory augmentation provides novel opportunities to broaden our knowledge of human perception through external sensors that record and transmit information beyond natural perception. To assess whether such augmented senses affect the acquisition of spatial knowledge during navigation, we trained a group of 27 participants for six weeks with an augmented sense for cardinal directions called the feelSpace belt. Then, we recruited a control group that did not receive the augmented sense and the corresponding tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 132 publications
0
0
0
Order By: Relevance
“…After the training period, while the participants continued to use the belt, an elaborate behavioral experiment followed in which we assessed the participants' spatial knowledge acquisition compared with a control group. The results of these measurements after the training period are published in Schmidt et al (11). Here, we will focus on the previously unpublished data recorded during the training period.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…After the training period, while the participants continued to use the belt, an elaborate behavioral experiment followed in which we assessed the participants' spatial knowledge acquisition compared with a control group. The results of these measurements after the training period are published in Schmidt et al (11). Here, we will focus on the previously unpublished data recorded during the training period.…”
Section: Methodsmentioning
confidence: 97%
“…The specific context and what kind of augmented sensory information is processed and learned is also important to consider when studying the acquisition of a novel sense, as it would likely affect the creation of SMCs. Previous research showed qualitative and quantitative differences in how well individuals can process information from the augmented modality (11,12). A fairly direct application to study the effect of obtaining a novel sense is the field of space perception.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35,45], but cf. [46] for use of a 'virtual wand' to enable 3D-pointing in VR and [47] for a virtual building placement task).…”
Section: Evolving the Pointing Task: Embedded 3d Marker Placementmentioning
confidence: 99%
“…All data and analysis scripts are available at OSF (131). The repository additionally contains the project documentation and the VR exploration and VR task assessment Builds for replication or incorporation in novel experiments.…”
Section: Data Availabilitymentioning
confidence: 99%